2004
DOI: 10.1007/s10595-005-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of fatty acids from solutions in organic solvents on the surface of finely dispersed magnetite: 1. Isotherms of adsorption of oleic, linoleic, and linolenic acid from carbon tetrachloride and hexane

Abstract: Isotherms of adsorption of oleic, linoleic, and linolenic acids on magnetite from solutions in carbon tetrachloride and hexane are measured. When CCl 4 is used as a solvent, the adsorption values increase in the following order: oleic, linoleic, and linolenic acid. In the case of hexane, the order is opposite. Adsorption isotherms of the fatty acids on aggregated magnetite are described in terms of the theory of volume filling of micropores. It is disclosed that, in the case of CCl 4 , the limiting adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…As was shown earlier [14], the dissolution of studied fatty acids in CCl 4 and hexane is accompanied by their solvation; hence, it should be expected that, in these…”
Section: Adsorption Of Fatty Acids From Solutions In Organic Solventssupporting
confidence: 60%
See 2 more Smart Citations
“…As was shown earlier [14], the dissolution of studied fatty acids in CCl 4 and hexane is accompanied by their solvation; hence, it should be expected that, in these…”
Section: Adsorption Of Fatty Acids From Solutions In Organic Solventssupporting
confidence: 60%
“…Finely dispersed magnetite was prepared according to [14]. A highly sensitive automatic differential titration calorimeter designed for detecting the low heat effects of endo-and exothermic processes [15] was used to measure the heats of fatty acid adsorption on magnetite surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two last compounds are classified as essential acids of the vitamin F group, which are also used as ad sorbates to provide aggregative and sedimentation stabil ity of magnetic liquids. [4][5][6][7][8] These UFA are interesting, first of all, due to the fact that their "long chain" molecules contain the same num ber of carbon atoms (C 18:n ) but differ in the number of double bonds n C=C in the cis 3 , cis 6 , and cis 9 posi tions with respect to the terminal methyl group. 1,2 There fore, each of the compared UFA has specific features governing solvation in solutions.…”
mentioning
confidence: 99%
“…[6][7][8][9] Previously, 7 we studied the heats of solvation of oleic and linoleic acids in n hexane to establish the solvating power of nonpolar solvents with respect to UFA. It is shown that the solvation process becomes less endother mic with an increase in n C=C in an acid molecule.…”
mentioning
confidence: 99%